RESEARCH OF MYCOBACTERICIDAL ACTIVITY OF CONTINUOUS SPECTRUM PULSED ULTRAVIOLET LIGHT - V. I. Litvinov; S. G. Safonova; G. E. Freyman; E. P. Selkova; T. A. Grenkova; M. P. Gusarova (Туберкулез и болезни лёгких)
The article presents the experimental studies results of continuous spectrum pulsed UV light mycobactericidal activity against the laboratory strain of Mycobacterium terrae and clinical strains of Mycobacterium tuberculosis with multiple and extensive drug resistance. A pulsed xenon lamp of a mobile “Alfa-01” unit for air decontamination was used as ultraviolet light source. The experiments showed high activity of pulsed UV light against all studied strains, which does not depend on the distance to the treated surface (up to 4 m). The efficiency of contaminated surfaces disinfection reached 100%. Exposing contaminated objects to pulsed xenon UV lamps’ light leads to multiple molecular genetic changes in DNA macromolecules with complete loss of drug resistance to rifampicin and partial loss of drug resistance to isoniazid.